Radio-ablative iodine therapy for Thyrotoxicosis: The Universiti Kebangsaan Malaysia Medical Centre (UKMMC) experience - Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Abd Aziz, Aini; AR, Anilah; Ooi, CP; M., Azura Dina; Zainuddin, Suehazlyn; Abd Wahab, Norasyikin; Mustafa, Norlaila; Sukor, Norlela; Kamaruddin, Nor Azmi (ASEAN Federation of Endocrine Societies, 2013)
Background: Radio-ablative iodine (RAI) is one of the treatment of choice for thyrotoxicosis. This study was done to determine the remission rate of thyrotoxicosis after radio-active iodine-131 (RAI) therapy and the factors associated with repeat RAI therapy at our centre. Methods: This was a retrospective analysis of 69 thyrotoxic patients who received RAI therapy from January 2011 until December 2011 in UKM Medical Centre. They were followed up for a period of two years. Data was analyzed using SPSS v.20. Results: Sixty-nine patients received RAI therapy in 2011. The mean age of the patients was 42.1 ± 12.4 years. Mean thyroxine level prior to RAI was 28.9 ± 12.8 pmol/L, and majority (80.3%) had suppressed TSH (<0.01 mIU/L) while 19.7% had low but detectable TSH (0.01-0.3 mIU/L). Ten percent of patient received second RAI within the 2 years follow-up period. Fifty-five percent of patients received 12 mCi of RAI, 24.6% and 20.3% received 10 and 15 mCi respectively. Fifty-two percent of patient remained hyperthyroid at 6 months post RAI (62% have suppressed TSH, 38% had detectable low TSH). Eighteen percent (17.9%) of patients became euthyroid and one third (30.4%) became hypothyroid at 6 months. At 12 months 62.7% of patient went into remission where 37.5% of them were euthyroid and 62.5% were hypothyroid. We did not find any difference between those who received single RAI compared to second RAI in terms of age, ethnicity, gender, anti-thyroglobulin and anti-thyroid peroxidase titre, or free thyroxine (T4) and TSH level prior to the RAI. Conclusions: The percentage of remission after RAI therapy at our centre is 48% at 6 months and 62.7% at 12 months. The requirement for second RAI was not associated with age, ethnicity, gender, anti-thyroglobulin and anti-thyroid peroxidase titre, free T4 and TSH level.